Exploring the Performance of Path Reliability in MANETs Through an Energy-Efficient RRS Algorithm - Vijay U. Rathod; Shyamrao V. Gumaste; Sameer S. Gajghate (Journal of Engineering)
A MANET consists of several nodes that dynamically move to change the network topology. In this paper, a novel energy-efficient RRS algorithm has been proposed. Our proposed algorithm seeks to improve network connection and energy efficiency concurrently. The neighbor node with the highest energy among all the neighbor nodes is always chosen using the proposed approach. In a dynamic network, the intermediate nodes rapidly exhaust energy since they receive and send data. The proposed algorithm decides which of these nodes to use based on the section representing their remaining maximum energy level to better use the node’s energy for a longer lifespan. After obtaining each request’s response, the sender selected the most significant energy node available for data transmission. The proposed energy-efficient algorithm improves network performance compared to existing routing protocols such as AntNet, EE-OLSR, and OLSR. Performance indicators like throughput, delay, packet loss, and PDR are used to assess the routing performance. As a result, there is an average 3.25% gain in throughput performance, a 17.65% decrease in latency, a 27.59% drop in packet loss, and a 4.9% rise in PDR.